Fagopyrum dibotrys protects gut health in broiler chickens fed oxidized oil - Lulin Tan; Xue Han; Liang Li; Lina Li; Yulong Feng; Qingfeng Wang (Journal of Applied Poultry Research)
SUMMARY: The objective was to evaluate protective effects of Fagopyrum dibotrys (perennial buckwheat), antibiotics, or both, on gut health in broiler chickens fed oxidized soybean oil. Male Tiejiaoma broilers (n=240), at 1 d of age, were randomly and equally assigned to 4 treatment groups that were fed: a basal diet (Ctr group) or a diet with 60 mg flavomycin+270 mg chlortetracycline/kg diet (Anti group), with (Anti + Fag) or without 2% F. dibotrys (Fag group). In the present study, the inflammatory factor levels and gene expression levels were determined using commercial ELISA kits and qRT-PCR analysis, respectively. The mRNA expression profiles of ileal tissue were analyzed by RNA sequencing, and the cecal microbiota were sequenced using 16S rDNA amplicon sequencing. The Anti group had the best (P < 0.05) feed conversion ratio and greater (P < 0.05) body weight gain compared to Fag and Anti + Fag, In ileal tissue, the Fag group had significantly decreased concentrations of proinflammatory cytokines (IL-6, IL-1β, IFN-γ and TNF-α) but increased IL-22, and significantly increased mRNA expression of ZO-1, TNF-α, IFN-γ, TGF-β, IL-22, Nrf2, SOD1, and CAT. However, all these effects were reversed in the Anti + Fag group. Based on 16S rDNA, the Fag group had significantly increased microbial diversity in cecum, with a distinct microbiome based on principal coordinates analysis (PCoA), including increases in relative abundance of Firmicutes in phyla, and in genera Candidatus_Arthromitus, Streptococcus, Enterococcus, and Lactobacillus. However, those changes in cecal microbes did not occur in Anti + Fag group. Based on RNA-seq, there were 771, 2187, 825, 1774, 898, 2127 differentially expressed (DE) mRNAs detected between Anti vs Ctr, Fag vs Ctr, Anti + Fag vs Ctr, Fag vs Anti, Anti + Fag vs Anti, and Anti + Fag vs Fag, respectively. Based on Kyoto Encyclopedia of Genes analysis (KEGG), DE mRNA were enriched in categories and pathways related to gap junction, oxidative phosphorylation, ECM-receptor interaction, focal adhesion, as well as the PPAR, TGF-β, and calcium signalling pathways. In summary, F. dibotrys ameliorated the inflammatory response by regulating expression of TNF-α, IFN-γ, TGF-β and IL-22; enhanced antioxidant activity by increasing expression of Nrf2, SOD1, and CAT; facilitated growth of Candidatus_Arthromitus, Streptococcus, Enterococcus and Lactobacillus; and regulated gene expression profile and signal pathway enrichment in ileal tissue.